2008
DOI: 10.1590/s0103-50532008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory instabilities during the electrocatalytic oxidation of methanol on platinum

Abstract: Descreve-se neste artigo a observação experimental de dinâmica oscilatória durante a oxidação eletrocatalítica de metanol sobre platina. Além das, previamente relatadas, oscilações de potencial, oscilações de corrente obtidas sob controle potenciostático também são apresentadas. A região de existência de oscilações de corrente é mapeada no plano de bifurcação voltagem aplicada x resistência. Conjuntamente com investigações eletroquímicas, espectroscopia FTIR in situ também foi aplicada nestes estudos. Apesar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 42 publications
4
39
1
6
Order By: Relevance
“…[3][4][5][6][7][8][9][10] An important intermediate is HCO which has been shown to occupy three adjacent sites. It can be further dehydrogenated to CO, which subsequently reacts with adsorbed oxygen species ͑OH or O͒ to form CO 2 .…”
Section: Mechanism and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] An important intermediate is HCO which has been shown to occupy three adjacent sites. It can be further dehydrogenated to CO, which subsequently reacts with adsorbed oxygen species ͑OH or O͒ to form CO 2 .…”
Section: Mechanism and Modelmentioning
confidence: 99%
“…A promising candidate as energy source is methanol for so-called direct methanol fuel cells 2 on which numerous mechanistic and kinetic studies have been carried out. [3][4][5][6][7][8][9][10] The oxidation of MeOH on noble metal electrodes ͑Pt or Pt/Ru͒ is known to exhibit kinetic instabilities, e.g., under galvanostatic conditions the process exhibits kinetic oscillations as well as a hard transition to high potential. 4 Such dynamic instabilities can be exploited for model development as will be shown in the present study where we identify the core mechanism explaining the experimentally observed bifurcation sequence.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 As in the case of many small organic molecules, 27 the electro-oxidation of methanol is known to display potential/ current oscillations under some circumstances. [28][29][30][31][32][33][34][35][36][37] The main aspect to be pointed out in Fig. 3 is certainly the presence of additional peaks for the CO 2 production for each potential oscillation.…”
mentioning
confidence: 99%
“…[1][2][3] Particularly in the case of low temperature fuel cell relevant reactions, such as the catalytic electrooxidation of hydrogen and small organic molecules, oscillatory dynamics seems to be a rule rather than an exception. [4][5][6][7][8][9][10][11] Current and potential oscillations during the electro-oxidation of hydrogen have been very often observed since the first half of the last century. [12][13][14][15][16][17][18][19] The current understanding of this reaction is that oscillations arise due to the overlap between two potential-dependent adsorption isotherms.…”
mentioning
confidence: 99%